Atención al cliente de la empresa "Jave Jireth" de la ciudad de Babahoyo. - Acosta Acosta, José Georgintong (2022)
This case study was carried out in the company "JAVE JIRETH" in the city of Babahoyo in order to know if the company's customer service is adequate, where the development of this investigative work was granted through the surveys carried out. customers that the company does not carry out any type of measurement to know if they feel satisfied. To carry out this research, techniques such as the survey were used, since it allows the collection of sufficient information to know the point of view of the people who buy in this place week by week, for this an alternative solution will be created so that the administrators can implement to improve the profitability of the commercial and therefore have higher sales. In this case study, the importance of knowing the point of view of the clients to promote their loyalty was described, as well as how this affects a company, and whether it is small or large, each business should know its clients.